The role of plants, bacteria, and fungi in carbon transfer from atmospheric CO2 to calcium carbonate through the oxalate-carbonate pathway - (:unkn) unknown (My University, 2025)
Pluri-disciplinary by definition, this proposal uses microbiological, molecular, and biogeochemical techniques in order to understand, evaluate, and measure the potential the role of plants, bacteria, and fungi in carbon transfer from atmospheric CO2 to calcium carbonate through the oxalate-carbonate pathway. This phenomenon was discovered under tropical trees in normally carbonate-free acidic soils and could have a global importance for the transfer of atmospheric carbon dioxide to calcium carbonate, acting as a stable carbon sink. Such research requires a combination of field sampling and analyses, as well as laboratory experiments, orchestrated by scientists competent in geochemistry, mycology and bacterial ecology. These are the domains of the three applicants who have worked together interdisciplinarly for several years. In addition, this project deals with a fundamental terrestrial pathway that has been completely overlooked in recent reports (IPCC, 2007). Based on our results up until now, we know that the scientific repercussions of this proposal could be enormous. Our aim is to understand, quantify, and use the oxalate-carbonate pathway as a possible and significant contributor to solve the problem of the atmospheric CO2 increase. Our recent work on oxalotrophic bacteria has allowed us to detect rapidly and specifically the presence of oxalotrophic bacteria in complex environmental samples without a biased cultivation step. We plan to develop molecular tools to quantify and identify the various bacterial guilds involved in the oxalate-carbonate pathway. In addition, we plan to develop an experimental approach using Petri dishes and microcosms in order to follow and quantify the processes involving oxalate producers (fungi) and consumers (bacteria). These experiments will introduce a kinetic baseline for calcium carbonate production and results will be compared with field data. In conclusion, this phenomenon of global importance is controlled by a sequence of biotic and abiotic factors, i.e. (i) plants, in which calcium oxalate accumulation is well documented, (ii) fungi, a number of which produce calcium oxalate from organic matter, but also participate to the decay of plant litter to expose plant oxalate crystals to degradation, and finally (iii) soil, which may modulate the extent of accumulation of calcium carbonate. The project aims to focus on the less documented steps of this pathway, namely the role of fungi, the function of the oxalotrophic bacterial guilds as a bioreactor of the transformation, and the role of bedrock (parent-rock) and soil, both as calcium sources and places of calcium carbonate accumulation.
Keywords: Biomineralization; Calcium carbonate; Calcium oxalate; Carbon pools and sequestration; Oxalotrophic bacteria; Fungi; Carbon pools; Carbon sequestration